Enhancement of chromatographic spectral technique applied to a high‐speed train. Issue 12 (12th September 2021) - Bustos, Alejandro; Rubio, Higinio; Castejon, Cristina; Garcia‐Prada, Juan Carlos
Summary: High‐speed rail is a key player in people's mobility thanks to its speed and high safety standards. These high safety standards are supported by extensive maintenance (of both rolling stock and track) that applies the latest nondestructive and monitoring techniques. In that context, this work presents the enhanced graphical representation of state configurations (EGRSC) and enhanced chromogram of bands of frequency (ECBF) methods, which are the evolution of the graphical representation of State configurations and chromogram of bands of frequency techniques. A clearer nomenclature is defined for the configuration states of the EGRSC. The ECBF introduces a new variable threshold that allows discarding frequency regions with small power variations and a new color palette. These methods are used in the vibratory study of an in‐service high‐speed train to identify the operating condition of the train. To conduct that task, a set of accelerometers is installed on the axle box of a trailer axle of the train. Accelerometers are oriented into the three space directions: longitudinal, lateral, and vertical. Vibration signals are taken during the normal operation of the train and transmitted to and stored on a remote database. Vibration measures are collected before and after a major maintenance operation. The application of EGRSC and ECBF allows collecting information from thousands of vibration signals and to display that information intuitively and understandably. The analysis of EGRSC and ECBF results allows identifying several frequency regions with significant spectral power variations that are common to the three vibration directions studied. These patterns should be taken as a reference for future maintenance actions. Any unexpected behavior of these frequency regions would indicate the presence of a fault.